FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA PERAWAT DI RUMAH SAKIT - Dwijayanto, I Made Rio; Poetra, Ricky Perdana; Putra, Ryryn Suryaman Prana; Mangindara, Mangindara (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Based on the results of an initial survey conducted in March 2022, it was noted that the total number of nurses working at the Makassar Hajj Hospital reached 316 people. Nurse satisfaction is very important to know in order to improve the quality of service and also a positive attitude towards work will emerge. Job satisfaction of each nurse can be measured by the size of the gap between expectations and the reality received. The purpose of the study was to determine the factors that affect nurses' job satisfaction in the hospital. The research design used in this study was cross sectional. The research was conducted at Hajj Hospital Makassar. The research was conducted in April 2024. The study population was all nurses at the Makassar Hajj Hospital. The research sample amounted to 42 people. The sampling technique used Simple random sampling. Data analysis was performed univariate and bivariate. The results showed a relationship between salary (p value: 0.003) and promotion opportunities (p value: 0.023). It is recommended that hospital management can review the amount of nurses' salaries and the governance of Human Resources in the Hospital.Keywords: Salary, Job Satisfaction, Promotion